MORAL VIEWS OF IBN SINA - U. Dadajonov; M. Kholbekova; Yu. Kochkarova (International Engineering Journal For Research & Development, 2021)
The article covers the moral, social, scientific and theoretical views of Ibn Sina on the basis of “Hikmat buloqlari”, the human factor, its role in the development of society and the most pressing issues related to these issues.